Α, β-Thujone suppresses human placental choriocarcinoma cells via metabolic disruption. Issue 6 (June 2020) - Lee, Jin-Young; Park, Hahyun; Lim, Whasun; Song, Gwonhwa
Abstract : α, β-Thujone is a natural terpenoid found in many medicinal herbs, such as Artemisia absinthium (wormwood), that exhibits antioxidant, anti-diabetic, and anti-tumorigenic effects. α, β-Thujone has numerous functions; it serves as a food ingredient, cosmetic additive, and medicinal remedy. Although the therapeutic properties of α, β-thujone were previously revealed, a comprehensive description of the mechanisms of its anti-cancer potential in choriocarcinoma is yet to be provided. To our knowledge, this study is the first to demonstrate that α, β-thujone attenuates JEG3 and JAR choriocarcinoma cells through a caspase-dependent intrinsic apoptotic pathway. Moreover, α, β-thujone was demonstrated to induce a global mitochondrial defect and ER stress in choriocarcinoma by causing mitochondrial depolarization, calcium overload, and metabolic alterations, thereby leading to energy deprivation, which eventually contributes to the increase in apoptosis of choriocarcinoma cells. Herein, we also revealed the synergistic anti-cancer activity of α, β-thujone via its sensitization effect on paclitaxel in choriocarcinoma cells. Altogether, our findings suggest that α, β-thujone is a novel, natural pharmacological compound that can be used to treat human placental choriocarcinoma.